Fuzzy-Based Automatic Landmark Recognition in Aerial Images Using ORB for Aerial Auto-localization - Filho, Paulo Silva; Rodrigues, Marcel; Saotome, Osamu; Shiguemori, Elcio H. (Advances in Visual Computing, 2014)
Aerial navigation based on computer vision is a subject in constant development. It aims to identify the localization of an Unmanned Aerial Vehicle based on aerial images captured during flight. This paper employs a fuzzy-based application to identify landmarks, using the ORB algorithm, which uses descriptors for the neighborhood of keypoints to identify specific registered objects on a scene. In Addition to the keypoint matching from ORB, a fuzzy system is used to analyze each match, in order to guarantee the proper identification of the landmark.